The Feasibility of Using Virtual Reality and Eye Tracking in Research With Older Adults With and Without Alzheimer's Disease - Davis, Rebecca (Frontiers in Aging Neuroscience, 2021)
Aim. To examine the feasibility of using large scale spatial, self-mobile, virtual reality and eye tracking in older adults with and without Alzheimer’s disease (AD). Methods. Older adults with early stage AD (n = 38) and a control group without AD (n = 50) were asked to find their way in a large, projected VR simulation of a retirement community repeatedly over 10 trials for each of two days, while wearing eye tracking glasses. Feasibility measures, including tolerance, side effects, and ability to complete the VR and eye tracking were collected. This study reports the analysis of the feasibility data for the VR and eye tracking and comparison of findings between the groups. Results. Over 80% of the subjects were able to complete the VR portion of the study. Only four subjects, all in the AD group, could not use the joystick and were excluded. Withdrawal rate (18%) was similar between the groups (X2 (2) = 2.82, N = 88, p =.245) with most withdrawals occurring after the fourth trial. Simulation sickness incidence was similar between the groups. Only 60% of the subjects had completed eye tracking videos; more subjects in the AD group had complete eye tracking videos than the control group; X2 (1) = 7.411, N = 88, p=.006. Eye tracking incompletion was primarily due to inability to calibration issues. Conclusion. Virtual reality testing and eye tracking can be used in older adults with and without AD in a large-scale wayfinding task, but that there are some limitations.